Adaptasi Masyarakat dalam Menghadapi Banjir Rob di Kelurahan Nelayan Indah Kecamatan Medan Labuhan Kota Medan - Aisyah Rahma Saragih; Hairani Siregar (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Floods are defined as events where dry plains (not swamp areas) become inundated, this is caused by high rainfall and the topographical conditions of the area in the form of concave lowlands. Community understanding is in the form of actualized perceptual knowledge from attitudes or actions in dealing with floods. The results of people's attitudes or actions in dealing with floods are adaptation strategies in adjustments a result of environmental threats. The city of Medan is one of the areas that experiences flooding every rainy season, to be precise in Nelayan Indah Village. Therefore, flooding becomes the center of attention to be overcome in preventing a disaster from occurring. These various land uses are vulnerable to tidal flooding, especially those in coastal areas and directly adjacent to the beach. Water will flow to a lower place with the help of gravity. This is what causes sea water to inundate several low places in the coastal area of Medan Labuhan District. Nelayan indah Village has the potential as a tourist attraction. Such maritime and historical attractions. Because. Floods that hit the Nelayan latif Village area are called tidal floods or tidal floods that occur more than dua times a year. Therefore, the community adapts both socially, economically and environmentally. Keywords: Rob Flood, Adaptation, Strategy.